استخدام استراتيجية التعلم التعاوني المحوسب وأثرها على تحصيل الطلاب ودافعيتهم نحو مادة الرياضيات دراسة تجريبية ميدانية في فلسطين - M. Sulayeh, Yaman M.
Mathematics is considered one of the basic subjects in the school system because of its strong relation to our daily life whether it is seen or hidden. The literature review showed low achievement for students in this subject and their reluctance to learn it. Thus, there is a need to use suitable learning methods that make the student the center of the teaching- learning process. The study problem deals with a learning strategy that is based on students’ interaction with each other and linking it to technology which may lead to overcome the low achievement problem and increase the motivation towards math. This study aims to find out the effects of using computerized cooperative learning strategy on students’ achievement and their motivation toward math and their relation to the demographic factors. It also aims to identify the teachers’ expectations toward integration of the computerized cooperative learning strategy in teaching and learning math classes. To achieve the study aims, quasi-experimental method was used to compare between the experimental and control group. The research sample was selected from the grade eight students from the governmental schools in the directorate of Education in Tulkarem District in Palestine. Both quantitative and qualitative data were collected by using the math achievement test and the motivation questionnaire; in addition to the personal interviews. The descriptive and inferential analysis was used for the quantitative data (T-test for two independent variables, T-test for two dependent variables, and ANCOVA test) in addition to the qualitative data analysis. The study showed that the experimental group students achieve better than the control group in math achievement test. It also revealed that there are more positive attitudes and motivation for the experimental group in comparison with the control group. This means that the computerized cooperative learning strategy has positive effects on students’ achievement and improved their motivation towards math. When comparing male and female students, it was found that there was no significant difference concerning the math test achievement and the motivation. The study found that there were positive attitudes for both teachers and students towards integrating the computerized cooperative learning strategy in teaching math sessions. The study contributed to the increase in both students achievement and motivation towards math, as well as, it contributed and provided knowledge that may cover lack in studies related to teaching and learning strategies that helps teachers inside classroom. The study recommended for education persons and decision-makers to adopt effective procedures and provide the necessary facilities for real implementation for mathematics curriculum.